ADDITIONAL NOTES ON PLANCHONIA BREVISTIPITATA KUSW. (LECYTHIDACEAE) - KUSWATA KARTAWINATA (BRIN Publishing (Penerbit BRIN), 1998)
Planchonia brevistipitata Kusw. is re-described and Barringtonia belagaensis P. Ghantaranothai is reduced to a synonym of this species.